Wawasan Al-Qur’an Tentang Poligami Dalam Islam: (Perspektif Penafsiran Wahbah Al-Zuhaili, Amina Wadud dan Sayyid Quthb) - Sugiarto, Fitrah; Hotimah, Husnul; Nurwathani Janhari, M. (MADINAH, 2018)
This article will explain about polygamy which is widely misunderstood by some people. Polygamy is the marriage of a husband with more than one wife at the same time. The opposite of polygamy is monogamy. In the perspective of Islamic law, polygamy is limited to a maximum of four wives. There are two main verses that can be used as a reference for polygamy, namely QS. Al-Nisa’ [4] : 3 and QS. Al-Nisa’ [4] : 129. Polygamy has gone along with the history of mankind, so polygamy is not a new trend that appears suddenly. The most common polygamy is a man who has more than one wife at a time. This study uses qualitative and comparative methods, namely by providing descriptive interpretations of several commentators. It is repeatedly associated with Islam, it is mentioned in the books and Hadith that having more than one wife is indeed permissible for a man who meets certain conditions. One of the conditions for a man to practice polygamy is to be able to be fair to his wife regarding the division of time, wealth, and attention. Many people argue that the law of polygamy in Islam is sunnah. However, when viewed from a legal point of view, generally the scholars are of the opinion that the law of polygamy is not actually a sunnah, but is permissible or permissible. However, polygamy is certainly not something that can be done by anyone. When wanting to do polygamy, a man should first reflect on whether he has fulfilled the requirements to do it or not.